Hubungan Masyarakat dan Transformasi Layanan BPJS Kesehatan dalam Membangun Hubungan Masyarakat yang Solid - Martha, Zike (Idarotuna : Journal of Administrative Science, 2024)
This study examines the important role of Public Relations (PR) in building Community Relations and improving the quality of health services provided by social security providers in Sawahlunto, West Sumatra. This study specifically aims to analyze how PR practices affect community trust, awareness, and accessibility of health services in this historically valuable mining area. Using a qualitative approach, data were collected through in-depth interviews with key informants, including PR professionals, local community leaders, and health service providers. According to the findings, successful public relations campaigns not only raise knowledge of the health services that are offered to the general public, but they also promote more community involvement and stronger, more enduring bonds amongst stakeholders. According to the study's findings, public relations plays a crucial role in resolving community issues and encouraging the use of medical services, both of which eventually improve health outcomes. These results highlight the value of PR in the larger framework of providing health and social security services, particularly in light of the particular difficulties faced by the mining industry.